BIMBINGAN DAN PENYULUHAN TENTANG TEKNIK PENYAJIAN BARANG DAGANGAN PADA BISNIS RITEL UNTUK PEMBERDAYAAN KARANG TARUNA RW 21 KELURAHAN PURWANTORO KOTA MALANG - Fullchis Nurtjahjani; Masreviastuti Masreviastuti (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2017)
Nowdays, retail bussineses are emerging as a result of society lifestyle that begin to change. The keypoints to increase the sales in the retail business is to sell or supply the wares with good quality, provide wares on many variation, display the wares attractively, and ensure that the wares are available in a sufficient quantities.In RW 21 Kelurahan Purwantoro, the n70% of the population have a shop.The methods to make the guidance are separate in 3 ways that consists of: transfer of knowledge, discussion, and also problem solving. After the guidance was implemented, use can evaluated that the factor that resisted the training participants are mutually support to implement these activities. Based on observation it can be concluded that 96% of the material can be understandable by the participants of local society. This is shown by 90% of the 20 participants (19 people ), are leaving some question about wares-display management. The participants also able to arrange the lay out of wares in front of the other participants in order to satisfy the consumer. In order to improve our knowledge, softskills are given to the public and participants, and all of stakeholders must work together to make it happen about wares display management in the local area and also Malang City in general.